Playing 7 vs. 6 with an empty goal: Is it really an option for coaches? A comparative analysis between Portugal and the other teams during the Men’s European Handball Championship 2020 - Prudente, João Nunes; Cardoso, Americo Ramos; Rodrigues, Ana Jose; Mendes, João Noite; Fernando, Catarina; Lopes, Helder; Sousa, Duarte Filipe (Frontiers in Psychology, 2022)
The dynamic of changes in the rules in team games materialize from research and debate between experts and coaches before being implemented by the International Federations. In Handball, the last changes occurred in 2016, and one of them was to substitute the goalkeeper with an additional field player allowing teams to play “empty goal” while using the additional field player. This study aimed to analyze and characterize the use of the 7 vs. 6 strategical-tactical option for the attack in the 2020 Men’s European Championship. We also analyzed whether the game time and partial score influenced the use of 7 vs. 6 and its efficiency. Observational methodology and a mixed ad hoc instrument combining field format and category systems validated by experts were used. Data were taken from 28 matches involving teams in the first 12 positions in the 2020 Men’s European Championship. The total number of offensive sequences in an organized attack method in 7 vs. 6 with an empty goal (n=123) were analyzed. Sequential analysis techniques with lags, prospective and retrospective, and polar coordinate analysis were used. The results showed that a) these solutions had poor efficiency, except for the Portuguese National Team; b) teams using the 7 vs. 6 tactic option had no negative consequences or increased risk with the opponent response; c) partial score influenced the decision to use 7 vs. 6 strategic option, and d) game time was associated with 7 vs. 6 play options and detected patterns.